New Era of Pedagogic Learning: A Systematic Review - Henny Setiani; Yayat Ruhiat; Sofwatillah Amin; Rifda Cita Zulviah; Noerma Kurnia Fajarwati (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: The fourth industrial revolution was characterized by the pervasive application of technology in many spheres of daily life, including education. Regarding learning, technology is used to impart new information, not new beliefs or principles. This article investigates the concept of pedagogical learning as a potential alternative approach to learning in the modern era of digital technology. Methodology: The writing method uses a systematic review by drawing on previous research pertaining to 2019-2022. Findings: According to the study’s findings, digital pedagogy is an approach that is not only based on the teacher’s skills in using technology but also on how the teacher, in the role of a facilitator, uses technology to build thinking skills and develop students’ affective aspects. Learning centers on the students, and technology fosters a dynamic learning atmosphere. Learning, which is inquiry-based and requires students to observe and construct the existing reality, is made possible through technology. This will help develop a critical mindset, curiosity, empathy, and the desire to seek solutions to real- world problems; consequently, it will build knowledge and social intelligence. Learning in the digital age can be supplemented with an alternative approach called digital pedagogy. This approach seeks to cultivate young people capable of critical thinking, flexibility, and social intelligence to meet the challenges posed by the industrial revolution 4.0. Implications/Novel Contribution: The discipline of digital pedagogics arose from efforts to assist educators in developing the abilities required to thrive in the twenty-first-century classroom. The teacher’s ability to use technology is merely one component of the digital pedagogical method. This research provides insight into digital learning that will assist practitioners in understanding the value of digital learning and how it can be effectively applied .